ZnS on Cu2Te quantum dots: preparation, characterisation, and optimisation of photocatalytic/H2O2 process by response surface methodology. Issue 8 (21st June 2023) - Fatolahi, Leila
ABSTRACT: Fluoroquinolone antibiotic is used extensively and, is obtained to reasoninfluences neurologically on living microorganisms. In the present study, the photocatalyst/H2 O2 underUV light photo-degradation of Enrofloxacin was studied. In addition to that, ZnS on Cu2 Tequantum dots was gathered via a simple synthesis method. The ZnS/Cu2 Tenanocomposites were characterizedby dynamic light scattering, X-ray diffraction, scanning electron microscopy, and UV-vis spectroscopytothe evaluation of theoptical, and morphological properties.The Box-Behnken design method was used for Experiments optimizationusing response surface methodology (RSM). Several factors like ZnS/Cu2 Teconcentration, H2 O2 concentration, and initial pH on the optimisation ofEnrofloxacinphoto-degradation were evaluatedwiththe polynomial regression method. At optimum process factors (ZnS/Cu2 Te: 50 mg/L, H2 O2 : 100 mg/L, and pH: 6), the Enrofloxacinphoto-degradation was achieved 84.58% during 40 min as process time.The photo-degradationanalyzed for severaldecompositionprocesseslike as, H2 O2, UV/H2 O2, UV+ZnS/Cu2 Te, and UV+ZnS/Cu2 Te+H2 O2 were carried out at the optimum factors. In this study, the Statistical evaluation was carried out for the optimisation of photo-degradation processes for the removalof pharmaceutical wastewater.